Powder-Bed Stabilization for Powder-Based Additive Manufacturing. (16th June 2014) - Zocca, Andrea; Gomes, Cynthia M.; Mühler, Thomas; Günster, Jens
Abstract : The most successful additive manufacturing (AM) technologies are based on the layer-by-layer deposition of a flowable powder. Although considered as the third industrial revolution, one factor still limiting these processes to become completely autonomous is the often necessary build-up of support structures. Besides the prevention of lateral shifts of the part during the deposition of layers, the support assures quality and stability to the built process. The loose powder itself surrounding the built object, or so-called powder-bed, does not provide this sustenance in most existent technology available. Here we present a simple but effective and economical method for stabilizing the powder-bed, preventing distortions in the geometry with no need for support structures. This effect, achieved by applying an air flow through the powder-bed, is enabling an entirely autonomous generation of parts and is a major contribution to all powder-based additive manufacturing technologies. Moreover, it makes powder-based AM independent of gravitational forces, which will facilitate crafting items in space from a variety of powdery materials.